A person-centered exploration of athlete burnout across a competitive season - DeFreese, J. D.; Smith, A. L. (Journal of Clinical Sport Psychology, 2021)
Person-centered investigations of athlete burnout have utility to unearth novel information about this developmental experience within the social environment of competitive sport. Guided by extant theory, conceptually proposed developmental patterns of athlete burnout were examined across a season as expressed in profiles of emotional and physical exhaustion, reduced accomplishment, and sport devaluation perceptions. Athlete social perceptions were also explored as predictors of profile membership. Collegiate athletes (N = 129) completed established assessments of study variables at four in-season time points. Latent profile analysis revealed profiles characterized by athletes experiencing the three burnout dimensions similarly at any given time point, with the notable exception of exhaustion being more frequently experienced in some profiles. Social support perceptions predicted profile membership with moderate success. Trends in profile stability provide some support for consideration of exhaustion-driven burnout experiences. Results shed light on the theoretical pathways of burnout development and inform continued longitudinal burnout research efforts.